Log horizon : The West Wind brigade. 11 - Touno, Mamare; Koyuki (Manga artist) (Yen Press, 2019)
An unforeseen counterattack from the equipment hunter leaves soujirou in a pinch. But just when all hope seems lost, a revived kuroe comes to his rescue-with the power she's gained from her friends! As this battle to the death draws to a close, what will soujirou and the west wind brigade lose...and what will they gain?